2020
DOI: 10.3390/molecules25030764
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Anticancer Cytotoxicity of Azaaurones Overcoming Multidrug Resistance

Abstract: The resistance of tumors against anticancer drugs is a major impediment for chemotherapy. Tumors often develop multidrug resistance as a result of the cellular efflux of chemotherapeutic agents by ABC transporters such as P-glycoprotein (ABCB1/P-gp), Multidrug Resistance Protein 1 (ABCC1/MRP1), or Breast Cancer Resistance Protein (ABCG2/BCRP). By screening a chemolibrary comprising 140 compounds, we identified a set of naturally occurring aurones inducing higher cytotoxicity against P-gp-overexpressing multidr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…By contrast, aurone derivatives were far less active, although they shared similar selectivity ratios. Higher IC 50 values of 60 μM and 15.0 μM were recorded for compound 17 , one of the best aurones in the series . Surely, more work is needed for improving the modest observed ratios and to further assess the true potential of the hemiindigoid family at targeting collateral sensitivity.…”
Section: Biological Activities Of Hemiindigoidsmentioning
confidence: 99%
“…By contrast, aurone derivatives were far less active, although they shared similar selectivity ratios. Higher IC 50 values of 60 μM and 15.0 μM were recorded for compound 17 , one of the best aurones in the series . Surely, more work is needed for improving the modest observed ratios and to further assess the true potential of the hemiindigoid family at targeting collateral sensitivity.…”
Section: Biological Activities Of Hemiindigoidsmentioning
confidence: 99%
“…(Z)-2-ylideneindolin-3-ones, namely aza-aurones, represent an interesting class of heterocyclic enones showing a broad range of applications in medicinal chemistry and in material sciences. Therefore, aza-aurones demonstrated potential applications as antimalarial, 1,2 antituberculotic 3 and anticancer agents 4 and, because of their peculiar photochemical behaviour, they have recently been studied as photoswitching systems. [5][6][7][8] However, aza-aurones are also known as powerful synthetic building blocks for cycloaddition reactions both as heterocyclic dienes, furnishing a "four-atom" unit, [9][10][11][12] or by reacting at the exocyclic double bond, providing an easy access to 3-oxo-2spiroannulated indolines (spiropseudoindoxyls) by [n+2] processes.…”
Section: Introductionmentioning
confidence: 99%
“…The multidrug resistance (MDR) of tumors [ 76 ] was one of the leading causes of clinical chemotherapy failure, but the mechanism of drug resistance of tumors has yet to be fully elucidated. Currently, p-glycoprotein (P-GP), MDR-associated protein 1 (MRP1), and breast cancer drug resistance protein (BCRP) are recognized to be closely related to MDR [ 77 ]. In addition, studies have shown that extracellular vesicles (EVs) are involved in the communication between MDR cells and drug-sensitive cells, promoting the spread of the MDR phenotype.…”
Section: Resultsmentioning
confidence: 99%